Application of fractal models for determining the relationship between REEs and faults in North Kochakali coal deposit, Central Iran - Mojtaba Bazargani Golshan; Mehran Arian; Peyman Afzal; Lili Daneshvar Saein; Mohsen Aleali (Scientific Reports)
Abstract The purpose of this research is to use the Concentration-Distance (C-D) fractal model to determine the relationship between the concentrations of ƩREEs and faults in coal seams of the North Kochakali coal deposit. For this purpose, three Concentration-Distance fractal models including: ƩREEC–DDF, ƩREEC-DSF, and ƩREEC– DTF were created based on ƩREEs concentrations and the distance from dextral, sinistral, and thrust faults, respectively. Four different geochemical populations were obtained according to fractal diagrams. The ƩREEC –DDF fractal model indicate that the very high geochemical population that includes the highest concentrations of ƩREEs in coal seams are located at a distance of 36–76 m from dextral faults with normal component, which indicates a positive relationship between ƩREEs mineralization and the distance from the dextral faults. Therefore, dextral faults with normal component were determined as the main factor of ƩREEs enrichment in coal seams of North Kochakali. Dextral faults with normal component acted after the formation of coal seams in North Kochakali coal deposit. So, the mineralization of REEs in North Kochakali coal deposit is epigenetic. Finally, the Concentration-Distance fractal model can be used as a suitable method to isolate the main mineralization and detect the relationship between faults and mineralized zones.